Business development and bid management at Bangladesh Engineering & Construction Corporation Ltd. (BECC) - Faruqui, Minhaj Kamal (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.